Impaired metabolic health over‐time and high abdominal fat are prospectively associated with high‐sensitivity C‐reactive protein in children: The IDEFICS study. Issue 11 (25th June 2021) - González‐Gil, Esther M.; Moreno, Luis A.; Nappo, Annunziata; Santabárbara, Javier; Wolters, Maike; Russo, Paola; De Henauw, Stefaan; Veidebaum, Toomas; Molnar, Denes; Hunsberger, Monica; Fraterman, Arno; Iacoviello, Licia; et al.
Summary: Background: Metabolic risk and inflammatory state have an early life onset and are associated with future diseases. Objectives: To assess the association between metabolic syndrome (MetS) and metabolic health with high‐sensitive C‐reactive protein (hsCRP), cross‐sectionally and longitudinally, in children. Methods: 2913 European children (2‐10 years) from eight countries from the IDEFICS study were investigated. Data were collected at baseline and 2 years later (follow‐up). A MetS z‐score was computed with waist circumference (WC), insulin resistance index, blood pressure, high‐density lipoprotein cholesterol and triglycerides. Metabolically unhealthy (MU) status was assessed. Multi‐level linear and logistic regressions were performed. Results: Among the MetS markers, WC was more consistently associated with hsCRP cross‐sectional and prospectively. Baseline MetS score was significantly associated with greater risk of high hsCRP at follow‐up and with prevalence and incidence of hsCRP. Those children who became MU overtime were significantly ( P < .05) associated with future higher levels of hsCRP, independently of weight status at baseline. Conclusions: Transition over time to a MU state was associated with higher levels of hsCRP at follow‐up, independent of weight status at baseline. Screening of metabolic factors and routine measurement of WC are needed to prevent inflammatory status and related chronic diseases in children.